Phyto-Remediation Of Dairy-Waste Water Using Constructed Wetland - MR.J.S.SUDARSAN,; DEEPTHA THATTAI,; ASHUTOSH DAS, (International Journal of Pharma and Bio Sciences, 2012)
The search for cost-effective and eco-friendly ways to control water pollution has led to renewed interest in constructed wetlands. The constructed wetland studied herewith consisted of a basin or channel with a barrier to prevent seepage and with beds filled with a suitable depth of porous media. The media also supports the root structure of vegetation. Thus a constructed wetland was made to mimic the function of a natural wetland, and allowed to mature naturally for 12 days, planted with Typha species to treat diary-wastewater. The treatment resulted in significant reduction of BOD (73%), solids (including suspended, dissolved & volatile solids (75-83%) and phosphorus (75.7%), with moderate improvement in COD and ammonical nitrogen (about 26% in each of these cases). The plants used for phyto-remediation are found to show significant growth with regard to height (71-100%), number of leaves per plant (80-100%) and root-length(57-65%). growth was also observed.